2023
DOI: 10.3389/fnagi.2023.1096206
|View full text |Cite
|
Sign up to set email alerts
|

White matter injury, cholesterol dysmetabolism, and APP/Abeta dysmetabolism interact to produce Alzheimer’s disease (AD) neuropathology: A hypothesis and review

Abstract: We postulate that myelin injury contributes to cholesterol release from myelin and cholesterol dysmetabolism which contributes to Abeta dysmetabolism, and combined with genetic and AD risk factors, leads to increased Abeta and amyloid plaques. Increased Abeta damages myelin to form a vicious injury cycle. Thus, white matter injury, cholesterol dysmetabolism and Abeta dysmetabolism interact to produce or worsen AD neuropathology. The amyloid cascade is the leading hypothesis for the cause of Alzheimer’s disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 346 publications
(398 reference statements)
2
7
0
Order By: Relevance
“…Demyelination can lead to further neurodegeneration since myelination protects vulnerable denuded axons and provides bioenergetic and trophic support [ 50 , 66 ], which is of interest in neurodegenerative processes of Alzheimer’s disease [ 52 ]. Furthermore, myelin is highly enriched in cholesterol, which is emerging with apolipoprotein E as an important factor in white matter impairment in aging and neurodegenerative diseases [ 6 , 8 , 69 ]. Axon damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Demyelination can lead to further neurodegeneration since myelination protects vulnerable denuded axons and provides bioenergetic and trophic support [ 50 , 66 ], which is of interest in neurodegenerative processes of Alzheimer’s disease [ 52 ]. Furthermore, myelin is highly enriched in cholesterol, which is emerging with apolipoprotein E as an important factor in white matter impairment in aging and neurodegenerative diseases [ 6 , 8 , 69 ]. Axon damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol serves as a crucial constituent of myelin and synaptic vesicles, playing an indispensable role in synaptic plasticity as well as facilitating learning and memory processes within the brain [ 41 ]. Following neurodevelopment, cholesterol is unable to traverse the BBB and is primarily synthesized by astrocytes [ 11 ]. Compelling evidence suggests impaired cholesterol synthesis within the brain of AD patients [ 29 ], and intriguingly, abnormal deposition of cholesterol within tangled neurons has been observed in individuals with AD [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following neural development, cholesterol encounters restricted permeability across the blood-brain barrier (BBB) [ 10 ]. In the brain, astrocytes primarily undertake the synthesis of cholesterol [ 11 ]. Sterol regulatory element-binding protein 2 (SREBP2), a transmembrane protein, assumes a pivotal role as a transcription factor in the regulation of cholesterol synthesis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…APP accumulation was more prevalent in mild cases of white matter ischemia compared to moderate and severe cases of white matter injury, suggesting that APP immunoreactivity occurs in the early stage of white matter lesions. Further, “recent studies have shown abnormal white matter in every AD brain” ( Sharp et al, 2023 ). Although the characteristic AD plaques and tangles are found in gray matter, increased Aβ 40/42 peptides damage myelin, causing cholesterol release and cholesterol dysmetabolism contributing to Aβ dysmetabolism, and a vicious injury cycle ( Sharp et al, 2023 ).…”
Section: Macrocephaly Neuroinflammation and Appmentioning
confidence: 99%
“…Further, “recent studies have shown abnormal white matter in every AD brain” ( Sharp et al, 2023 ). Although the characteristic AD plaques and tangles are found in gray matter, increased Aβ 40/42 peptides damage myelin, causing cholesterol release and cholesterol dysmetabolism contributing to Aβ dysmetabolism, and a vicious injury cycle ( Sharp et al, 2023 ).…”
Section: Macrocephaly Neuroinflammation and Appmentioning
confidence: 99%